Peutz-Jeghers syndrome - Homan, Matjaž (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Peutz-Jeghers syndrome (PJS) is an unusual hamartomatous polyposis of the gastro intestinal (GI) tract, with pigmentation around lips and macules on thebuccal mucosa. The case of a 10-year-old girl who presented with intussusception is reported. A polyp was found to be the cause of an invagination. Histologically it was a hamartoma. PJS is a rare syndrome inherited in an autosomal dominant pattern. Most patients have recurrent episodes of polyp induced bowel intussusception which requires repeated laparotomies. In addition, these patients have an increased risk of malignant disease in gastrointestinal and also non-gastrointestinal sites. To prevent cancer and short bowel syndrome, aggressive screening is recommended. Upper and lower endoscopy should be performed every two years from 10 years of age. Extra-intestinal surveillance for cancers, including abdominal and pelvic ultrasound, as well as testicular and breast examinations once yearly should be introduced in the second decade of life.
Keywords: Child; Diagnosis; Gastrointestinal Neoplasms; gastrointestinalne bolezni; Gastrointestinalne novotvorbe; Hamartom; Hamartoma; kožne bolezni; otroci; Otrok; Peutz-Jeghers Syndrome; Peutz-Jeghersov sindrom; Therapy